MENGUKUR RENTABILITAS BANK PEMBANGUNAN DAERAH NTB DENGAN PENDEKATAN ROA - Rizky Amelia (J-ESA (Jurnal Ekonomi Syariah), 2018)
One of the assessment component of the bank performance is the assessment on rentability. The assessment on rentability measures the success of a bank in generating profits out of the total allocation assets. Profitability may be measured through four approaches, which one of that is Return of Assets (ROA) approach. This paper analyze the impact of CAR, BOPO, LDR, and NPL on ROA (A case study at BPD NTB in the periode of 2004-2011). This study used Ordinary Least Square Method. The result shows that CAR had a positive but not significant effect on ROA, BOPO had negative but significant effect on ROA, LDR had apositive but not significant effect on ROA and NPL had a negative but not significant on ROA.